Social network sites and tools framework for project based learning - Mohamud Abadalla, Saeed Mohamed (2012)
Project based learning nowadays is one of the significant approaches for the teaching and learning purposes. Social networking sites are also playing currently big role in student and youth life. The challenge is to explore and investigate how to integrate the needs of the lecturers and usage of the social networking sites in their projects. This study considers and focuses on the available social networking sites for the education purpose which can support the group project and project based learning. The research investigates the usage of the social networking sites for project based learning purposes. Currently, there is still a lack of researches which consider the educational benefits associated with social networking sites and project based learning. In order to investigate and identify which social networking sites and tools that can support the project based learning, the researcher identify student perspective in using Facebook, which is currently the most popular social networking site and the integration of Facebook group and other tools (Google Doc and Slide share) which can improve the implementation of the project based learning in the classroom. The researcher chose these three tools according to the result of the questionnaire and the literature review. The researcher administered pre-questionnaire and post-questionnaire for evaluation of learning experience of students before and after supporting of those social networking sites. Through statistical analysis using t-test, the combination of the Facebook group, Google doc and Slide share have a positive impact on student project based learning experience.